The dissection of genotype × tissue interactions in mud crab Scylla paramamosain indicates the sexual differences in parental selection - Wei Zhang; Wei Zhang; Zerun Xie; Zerun Xie; Zilin Zhao; Zilin Zhao; Wenxiao Cui; Wenxiao Cui (Frontiers in Marine Science)
Studying the impact of genotype, tissue type, and their interaction on key sexual factor expression provides valuable insights into the spectrum and consequence of sex differences, particularly for maternal and paternal selection in the breeding of crustaceans. However, the interactions between genotype and tissue types, and their ability to distinguish the sexual differences of mud crab Scylla paramamosain remain unclear. Here we employed additive main effects and multiplicative interaction (AMMI), split-plot analysis (SP), and genotype main effects and genotype × environment interaction (GGE) biplot analysis to examine genotype × tissue interactions related to sexual factors expression of S. paramamosain. SP and AMMI analyses underscored genotype, tissue type, and their interaction can significantly affect sexual factor expression in both female and male crabs. AMMI analysis highlighted that genotype × tissue interactions exerted the most substantial influence on sexual factor expression in the females, while genotype alone played the most critical role in the males. GGE biplot analysis revealed positive correlations between gonad and other tissues, with the ovary and intestine showing the greatest discriminatory power for sexual factors in the females and the males, respectively. Moreover, gene fru2 exhibited relatively high and stable expression in both sexes which would be the preferred breeding index. This comprehensive statistical analysis sheds new light on the intricate relationship between genetics and phenotypes underlying sexual differences in S. paramamosain, offering valuable insights for developing tailored breeding strategies in mud crab parental selection.